PRESENTING THE OTHERS IN ENGLISH - Khristianto Khristianto (University of Muhammadiyah Purwokerto, 2017)
English does not only belong to the natives. Its speakers even are dominated by the non-natives. This very fact ideally should be seen on books of English learning. This is a way to present English as a global language. The article is aimed to see the presentation of others in English from the books, New Cutting Edge.Based on the analysis, it was found out that the books have accommodated the non-natives. Others’ presence include the persons, their cultures, and talks. The names of the character in the books are various, reflecting their origins. The books are also culturally representative. They describe various unique cultures belong to the world. Finally, the books also adopt others’ English, like declaring that their English is also true. Thus, it concludes that the books have shown that English belong to the world, and claimed that all people and their cultures stand equally in the global interaction.